Perancangan Model Bisnis Cafe Zapateria - Peggy Hariwan; Inggi Silviatni (Forum Manajemen Indonesia (FMI), 2014)
The aim of this research is to plan business model for Zapateria’s cafe using BMC framework. Zapateria will be presented as example of development service cafe system which offer coziness, the simplicity of eat and shop which never been offered by other cafe. Moreover, the data exist showed the sum of people who visit Bandung for culinary and shopping with the number increase time to time. Those things are the reasons why this research made which are business model for cafe and shoes shop at one blow. Knowing the responses from the prospect of customers, which are adults, tourists, community, and shoes lover is the main aim of this research as a support in making business model plan that will be established. Qualitative method is the methodology used by the research which also triangulasi theory which are practitioners, expertise of cafe business, and experts in business field as data source. Direct interview to all source become technique to gather the data. The results analyzed and become indicator in empathy map. From the results of interview held show there are disappointment for miss delivery order and willingness of improvement for service offered by the exist cafe in Bandung by music performance in weekend and using gadget for integrated order from customer to the kitchen to reduce mistaken order and missing order. Final plan made from this research be expected can help development of business idea in Zapateria and other cafe. Keywords: Business Model, Business Model Canvas (BMC), Cafe, and Shoes